Politik und Propaganda in der modernen ungarndeutschen Literatur bis 1989 - Kerekes, Gábor (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
Political topics are relatively rare in Hungarian-German literature from the period up to 1989, which can be attributed to state surveillance – including of Hungarian-German literature. Only a few scattered works directly reflect communist propaganda, such as a praise poem about Lenin or texts that promote the narrative of humane and empathetic Soviet soldiers in the Second World War. Since it was not possible to directly and critically mention topics that were tabooed by the Hungarian state, even the expulsion of the Hungarian Germans in 1946-48 could only be cautiously mentioned in a narrative praising the communists. Until the 1980s, fundamental criticism of the political system was only possible in a veiled form, without directly naming the aspect being criticised.